Invasive Fungal Sinusitis Associated with Covid-19 - Hiral J. Hapani; Manek K Gadhvi; Kapil D Detroja; Anjana V Trivedi; Jagruti Kalola (Asian Journal of Medical Radiological Research, 2021)
Background: The world today facing unprecedented catastrophe in the form of a global pandemic of COVID-19 infection caused by the novel corona virus SARS-CoV-2(severe acute respiratory syndrome -corona virus-2).(3,n.d.) As most of the patients infected with COVID-19 are in the elderly age group having co-morbidities like diabetes mellitus or are immunocompromised. They are endangered to the development of various co-infections which are more common in patients with this type of clinical profile. Invasive fungal sinusitis is one of the co-infections primarily affecting paranasal sinuses, nasal cavity, orbit, brain and lungs. Common fungi causing invasive fungal sinusitis are Aspergillus, Mucor and Candida. In this article we are going to describe the major imaging findings of invasive fungal sinusitis in addition to the clinical picture which would aid in earliest diagnosis of this infections and allows radiologist to play an important role in patient management. Subjects and Methods: A Retrospective study with 30 patients over period of 3 months using MRI as diagnostic modality and tissue biopsy for the confirmation. Consent for participation in the study was obtained from each patient or their relatives. All COVID-19 infected patients suspected of fungal sinusitis referred for MRI paranasal sinuses, Orbit or Brain were included in the study. There were no definite exclusion criteria except in the cases where MRI was contraindicated. Results: Total 30 COVID-19 positive patients with suspicion of fungal infection were evaluated. Many patients had associated co-morbidities like diabetes, obesity, hypertension, steroid, chemotherapy or on long term COVID treatment. On MRI majority of patients had involvement of bilateral maxillary and ethmoid sinuses with bony erosions. 7 patients (23.3%) had shown spread to retro antral and orbital fat. 2 patients (6.6%) had shown orbital compartment syndrome with cavernous sinus thrombosis. On biopsy 21 patients (70%) confirmed with mucor, 7 (23.3%) patients confirmed with Aspergillus and 2 patients (6.6%) biopsy results were inconclusive. Conclusion: MRI findings were neither sensitive nor specific for invasive fungal sinusitis but it found to be useful for early diagnosis and showing its spread to the adjacent structures and brain. Contrast enhanced MRI was found to be better in characterization of the extent of spread of the disease and assessment of venous sinus thrombosis compared to Non-contrast MRI.